If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5x + 4(x + 3) = 0 Reorder the terms: 2x + 5x + 4(3 + x) = 0 2x + 5x + (3 * 4 + x * 4) = 0 2x + 5x + (12 + 4x) = 0 Reorder the terms: 12 + 2x + 5x + 4x = 0 Combine like terms: 2x + 5x = 7x 12 + 7x + 4x = 0 Combine like terms: 7x + 4x = 11x 12 + 11x = 0 Solving 12 + 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 11x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 11x = 0 + -12 11x = 0 + -12 Combine like terms: 0 + -12 = -12 11x = -12 Divide each side by '11'. x = -1.090909091 Simplifying x = -1.090909091
| -3/10x=-6 | | 5y-(7y+10)=7-(9y-6) | | 5=3x-50 | | a/5-2=7 | | 4*x-1=5 | | 5y+2y-16=3y+6-5 | | 17-20g=(13-5g)4 | | 40+15+0.25m=45+0.35m | | 12b+4+2= | | -5(-7x-10)=-39(5+7x) | | 9/8(m-57)=9/8(m-57) | | 1/5(d-200)=575 | | 3x+9=(x-2) | | (x^7/2)^3/7=8 | | (.10x+15)=(.15x+10) | | 16-15y=4 | | (2/3)g-4=(1/2)-2g | | 7-5(-6n-8)=14-3n | | -6(8x+1)=138 | | 5(y-4)/2=-4y | | f(x)=-3.25(-4.2)+22.41 | | 2/9t=8 | | 4(-3x+12)=6(8-2x) | | f(x)=-3.25x+22.41 | | 2y=x/2 | | 13.7b-6.5=-2.3b+83 | | -12*2/5 | | 10m+(0)=12 | | 6(x-4)=3x-24 | | 40.5p+14.40=4.50(p+3) | | 20+10x=4x-40 | | 10m+(-1)=12 |